Radical Scavenging by Acetone: A New Perspective to Understand Laccase/ABTS Inactivation and to Recover Redox Mediator - Hao Liu; Pandeng Zhou; Xing Wu; Jianliang Sun; Shicheng Chen (Molecules, 2015)
The biosynthetic utilization of laccase/mediator system is problematic because the use of organic cosolvent causes significant inhibition of laccase activity. This work explored how the organic cosolvent impacts on the laccase catalytic capacity towards 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) in aqueous solution. Effects of acetone on the kinetic constants of laccase were determined and the results showed Km and Vmax varied exponentially with increasing acetone content. Acetone as well as some other cosolvents could transform ABTS radicals into its reductive form. The content of acetone in media significantly affected the radical scavenging rates. Up to 95% of the oxidized ABTS was successfully recovered in 80% (v/v) acetone in 60 min. This allows ABTS recycles at least six times with 70%–75% of active radicals recovered after each cycle. This solvent-based recovery strategy may help improve the economic feasibility of laccase/ABTS system in biosynthesis.